The Effect of Strengthening Asking Skills with the Guided Inquiry Learning Model on Students Learning Outcomes on Rotation Dynamics - Yona Riska Amalia Ritonga; Edi Istiyono (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of strengthening questioning skills with the guided inquiry learning model on student learning outcomes. This type of research is quasi-experimental. The population in the study were all students of class XI semester II with a sample of class XI IPA 3 and class XI IPA 4, each of which consisted of 36 students. Sampling in this study was carried out randomly. The research design was a two group pre-test post-test design. The instrument used in the study was a multiple choice test consisting of 20 questions and post-test result with an average score of 76.94 for the experimental class and 70.13 for the control class. The result of the t-test stated that there was a significant influence between the learning outcomes of students who used strengthening asking skills with the guided inquiry learning model and learning without being given reinforcement of asking skills in class XI semester II students at Madrasah Aliyah.